Influenza A virus on oceanic islands: host and viral diversity in seabirds in the Western Indian Ocean. - Camille Lebarbenchon; Audrey Jaeger; Chris Feare; Matthieu Bastien; Muriel Dietrich; Christine Larose; Erwan Lagadec; Gérard Rocamora; Nirmal Shah; Hervé Pascalis; Thierry Boulinier; Matthieu Le Corre; et al. (PLoS Pathogens)
Ducks and seabirds are natural hosts for influenza A viruses (IAV). On oceanic islands, the ecology of IAV could be affected by the relative diversity, abundance and density of seabirds and ducks. Seabirds are the most abundant and widespread avifauna in the Western Indian Ocean and, in this region, oceanic islands represent major breeding sites for a large diversity of potential IAV host species. Based on serological assays, we assessed the host range of IAV and the virus subtype diversity in terns of the islands of the Western Indian Ocean. We further investigated the spatial variation in virus transmission patterns between islands and identified the origin of circulating viruses using a molecular approach. Our findings indicate that terns represent a major host for IAV on oceanic islands, not only for seabird-related virus subtypes such as H16, but also for those commonly isolated in wild and domestic ducks (H3, H6, H9, H12 subtypes). We also identified strong species-associated variation in virus exposure that may be associated to differences in the ecology and behaviour of terns. We discuss the role of tern migrations in the spread of viruses to and between oceanic islands, in particular for the H2 and H9 IAV subtypes.